The Impact of Emerging Technologies on Pharmaceutical Process Design and Optimization in Africa: A Review - (:unkn) unknown (My University, 2024)
Emerging technologies present a transformative potential for pharmaceutical process design and optimization, particularly within Africa’s evolving pharmaceutical industries. The purpose of this review is to explore the impact of emerging digital technologies, including Artificial Intelligence (AI), Machine Learning (ML), the Internet of Things (IoT), and Robotics, on pharmaceutical process design and optimization within the African context. Data was collected through a comprehensive literature review of scholarly articles, industry reports, and case studies. By analyzing recent advancements and case studies, this review identifies key areas where technology is reshaping the production processes for pharmaceutical product development. It highlights the benefits, including increased efficiency, improved accuracy, and minimized waste. However, the review also emphasizes significant challenges, including infrastructural limitations, regulatory barriers, and disparities in access to technology that can hinder the adoption of these emerging technologies in Africa. An assessment of their impact on manufacturing efficiency, drug production costs, drug quality, and safety reveals their potential to enhance pharmaceutical manufacturing operations significantly. The findings suggest that while emerging technologies offer substantial opportunities for improving pharmaceutical processes and operations, their successful integration requires a strategic approach that involves stakeholder cooperation, infrastructure improvements, and targeted capacity enhancement initiatives within the continent’s pharmaceutical industry. This review offers a broad overview of the current state of technological adoption in the pharmaceutical manufacturing sector in Africa and the impact of leveraging these emerging technologies to drive sustainable improvements in the pharmaceutical product development process.
Keywords: African Research